2011
DOI: 10.1007/s13238-011-1010-9
|View full text |Cite
|
Sign up to set email alerts
|

A structural view of the conserved domain of rice stress-responsive NAC1

Abstract: The importance of NAC (named as NAM, ATAF1, 2, and CUC2) proteins in plant development, transcription regulation and regulatory pathways involving proteinprotein interactions has been increasingly recognized. We report here the high resolution crystal structure of SNAC1 (stress-responsive NAC) NAC domain at 2.5 Å. Although the structure of the SNAC1 NAC domain shares a structural similarity with the reported structure of the ANAC NAC1 domain, some key features, especially relating to two loop regions which pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
82
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 50 publications
5
82
0
Order By: Relevance
“…Structure analysis of the SNAC1 NAC domain revealed structural similarities with the reported structure of the Arabidopsis ANAC NAC domain (Chen et al, 2011). To test whether SNAC1 can bind to the promoter of OsPP18, a genomic fragment of the OsPP18 promoter containing the CDBS located upstream of the start codon (Fig.…”
Section: Ospp18 Is Regulated By Snac1mentioning
confidence: 80%
“…Structure analysis of the SNAC1 NAC domain revealed structural similarities with the reported structure of the Arabidopsis ANAC NAC domain (Chen et al, 2011). To test whether SNAC1 can bind to the promoter of OsPP18, a genomic fragment of the OsPP18 promoter containing the CDBS located upstream of the start codon (Fig.…”
Section: Ospp18 Is Regulated By Snac1mentioning
confidence: 80%
“…Dimerization of DNA binding domains is common and can modulate the DNA-binding specificity [25]. Gel filtration studies on ANAC NAC domain [22] and SNAC1 NAC domain [21] have shown that in solution they exist as dimers that form the functional unit necessary for stable DNA binding [24]. We can reasonably presume that it is also the case for NAM-A1.…”
Section: D Conformation Of Nam-a1 Nac Domainmentioning
confidence: 95%
“…Prediction of the NAM-A1 NAC domain 3D structure was based on the crystal structure of the rice stress responsive NAC1 (SNAC1) NAC domain [21]. Crystallographic analysis of the NAC domain of the ANAC protein [22,23] encoded by the abscisic acid-responsive NAC gene from Arabidopsis thaliana and mutants study [24] were also used.…”
Section: D Conformation Of Nam-a1 Nac Domainmentioning
confidence: 99%
See 2 more Smart Citations